Single-cell RNA sequencing reveals a fibroblast gene signature that promotes T-cell infiltration in muscle-invasive bladder cancer - Zige Liu; Xingning Mao; Yuli Xie; Yunkun Yan; Xiang Wang; Junhao Mi; Hao Yuan; Jiange Zhang; Caisheng Huang; Jianxin Chen; Mujia Jili; Shengzhu Huang; et al. (Communications Biology)
Abstract Muscle-invasive bladder cancer (MIBC) is characterized by a complex tumor microenvironment (TME) that drives aggressive progression and treatment resistance. Previous studies have highlighted the roles of cancer-associated fibroblasts (CAFs) and exhausted T (Tex) cells in MIBC, but their interactive mechanisms remain poorly understood. Here, single-cell RNA sequencing of 19 tissue samples from 12 patients—7 MIBC, 3 non-muscle-invasive bladder cancer (NMIBC), and 9 normal tissue samples—identified 13 transcriptionally distinct fibroblast clusters and 10 functionally heterogeneous T-cell subsets. Two interferon (IFN)-responsive fibroblast populations, F-ISG15 (inflammatory CAFs) and F-POSTN (myofibroblastic CAFs), were shown to predominate in the MIBC TME. In vivo experiments demonstrated that IFN-γ secreted by Tex cells polarizes CAFs to secrete CXCL12, which recruits CXCR4-expressing T cells via the CXCL12-CXCR4 chemotactic axis. Spatial analysis revealed a bidirectional loop: Tex-derived IFN-γ sustains CAF activation, whereas CAF-secreted CXCL12 amplifies Tex infiltration. Clinically, activated CAF signatures correlate with advanced disease stages and reduced patient survival in MIBC. These findings establish CXCL12 and IFN signaling as critical therapeutic targets, offering new strategies to disrupt immunosuppressive TME crosstalk and improve outcomes for MIBC patients.